Improved modelling of high precision wide area differential GPS - Chao, Chih Hung Jason (1996)
Wide Area Differential GPS (WADGPS) aims at overcoming the main drawback of conventional DGPS, namely the limited range over which the differential corrections are valid, due to the rapid decorrelation of the error sources with increasing distance from the reference station to the user. In the WADGPS approach, error sources are generated for users over a large portion of the earth, such as a communication satellite's entire footprint, by separating and modelling the main sources of error in GPS measurements. This has the effect of eliminating the limit imposed on the validity of the corrections by the geographical or atmospheric environment. A main advantage of WADGPS is the fact that far fewer reference stations are needed to cover the same area, compared to conventional DGPS.